2021
DOI: 10.30782/jrvm.811350
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gender Factor on Mandibular Morphometry in Abaza Goats

Abstract: In In this study, the mandibles of Abaza goats were examined macroanatomically and morphometrically. A total of 14 adult (7 female / 7 male) Abaza goat mandibles of both sexes of different age and of body weight were used. Mandibles was removed from the head and cleaned of skin and rough meat, then macerated with hydrogen peroxide for 25-30 minutes and the lengths of 16 different points were measured by electronic caliper (0.00, BTS, UK) according to the literature. Mean, standard deviation and correlation val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…In contrast to the study on sheep and goats [27], Siirt-colored Mohair goats were found to have higher values of C8 parameter than sheep breeds. In addition, the mean value of the length between the GOV and the deepest point of the incisura mandibula (C12) parameter was smaller than the values determined in Hasmer sheep breed [38] and larger than the values determined in Abaza goats [17].…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…In contrast to the study on sheep and goats [27], Siirt-colored Mohair goats were found to have higher values of C8 parameter than sheep breeds. In addition, the mean value of the length between the GOV and the deepest point of the incisura mandibula (C12) parameter was smaller than the values determined in Hasmer sheep breed [38] and larger than the values determined in Abaza goats [17].…”
Section: Discussioncontrasting
confidence: 60%
“…This index was reported as 5.21±0.21 cm in Saanen goats [59], 4.77±0.19 cm in Markhoz goats [28], and 4.78±0.005 cm in Mizoram goats [7]. In addition, the skull index of Beetal goats was 5.73±0.01 cm in females and 5.77±0.01 cm in males [23], and the Abaza goats have been reported as 5.1±0.18 cm [17]. The skull index values determined in our study were lower than the reported goat breeds.…”
Section: Discussionmentioning
confidence: 96%